2020
DOI: 10.1136/bcr-2020-236264
|View full text |Cite
|
Sign up to set email alerts
|

4-month-old boy coinfected with COVID-19 and adenovirus

Abstract: A 4-month-old boy with a history of muscular ventricular septal defect and atopic dermatitis presented with decreased oral intake, loose stools, stuffy nose, mild cough and diaphoresis. The patient had an in-home exposure to COVID-19. The initial respiratory pathogen panel was positive for adenovirus, consistent with his symptoms. The following day, the COVID-19 PCR was also positive. The patient was treated with supportive care, isolation precautions were implemented and the patient was discharged on day 4. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…To date, coinfection of adenovirus and SARS‐CoV‐2 has been reported in a limited number of patients over 15 years of age and adults 20,50,51 . A case report of adenovirus coinfection with SARS‐CoV‐2 in a 4‐month‐old infant negated the misconception regarding the unlikelihood of adenovirus coinfection in infants, indicating that complete screening for COVID‐19 in addition to other virus infections, in this particular case, significantly reduced the risk of being an asymptotic carrier 80 …”
Section: Introductionmentioning
confidence: 94%
“…To date, coinfection of adenovirus and SARS‐CoV‐2 has been reported in a limited number of patients over 15 years of age and adults 20,50,51 . A case report of adenovirus coinfection with SARS‐CoV‐2 in a 4‐month‐old infant negated the misconception regarding the unlikelihood of adenovirus coinfection in infants, indicating that complete screening for COVID‐19 in addition to other virus infections, in this particular case, significantly reduced the risk of being an asymptotic carrier 80 …”
Section: Introductionmentioning
confidence: 94%
“…The most important finding of the present study is that we described an example of co-infection with SARS-CoV-2 and HAdV among some pneumonia patients with obvious epidemiological relationship. Previous studies have reported sporadic cases caused by co-infections of SARS-CoV-2 with other pathogens, including influenza A virus, respiratory syncytial virus, metapneumovirus, rhinovirus, and HAdV (8)(9)(10)(11)(12). The detection of SARS-CoV-2 co-infection with other respiratory viruses is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 co-infection alongside other pathogens have been reported, including occasional co-infections involving human adenovirus (HAdV) and SARS-CoV-2. However, reports of co-infections are rare (8)(9)(10)(11)(12). Moreover, little is known regarding whether SARS-CoV-2 co-infections are transmitted between individuals at rates capable of causing clusters of acute respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood infection with SARS-CoV-2 may range from an asymptomatic individual to upper respiratory tract infection, skin rashes, pneumonia, gastrointestinal upset, acute respiratory distress syndrome, nervous system involvement, rhabdomyolysis, and the newly recognized Kawasaki disease like presentation of Multisystem Inflammatory Syndrome in Children [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated prolonged fecal shedding of SARS-CoV-2 virus in children who have apparently recovered from COVID-19, raising the possibility of children acting as major sources of disease spread among communities [17]. Moreover, there are reports of children being coinfected with SARS-CoV-2 along with other viruses, which may have caused the presence of COVID-19 to be overlooked and subsequent isolation precautions neglected [8].…”
Section: Introductionmentioning
confidence: 99%